a) \(A=\left(\dfrac{x^2-2x}{2x^2+8}-\dfrac{2x^2}{8-4x+2x^2-x^3}\right)\left(1-\dfrac{1}{x}-\dfrac{2}{x^2}\right)\)
\(\Leftrightarrow A=\left(\dfrac{x^2-2x}{2\left(x^2+4\right)}-\dfrac{2x^2}{4\left(2-x\right)+x^2\left(2-x\right)}\right)\left(\dfrac{x^2-x-2}{x^2}\right)\)
\(\Leftrightarrow A=\left(\dfrac{x^2-2x}{2\left(x^2+4\right)}-\dfrac{2x^2}{\left(2-x\right)\left(4+x^2\right)}\right)\cdot\dfrac{x^2-x-2}{x^2}\)
ĐKXĐ: \(x\ne0;x\ne2\)
\(\Leftrightarrow A=\left(\dfrac{-x\left(2-x\right)^2-4x^2}{2\left(x^2+4\right)\left(2-x\right)}\right)\cdot\dfrac{x^2-x-2}{x^2}\)
\(\Leftrightarrow A=\dfrac{-x^3-2x^2-4x}{2\left(x^2+4\right)\left(2-x\right)}\cdot\dfrac{x^2-x-2}{x^2}\)
\(\Leftrightarrow A=-\dfrac{\left(x^2+2x+4\right)\left(x+1\right)\left(x+2\right)}{2\left(x^2+4\right)\left(2-x\right)}\)